Effect of heating rate and annealing temperature on secondary recrystallization of goss grains in a grain orientated silicon steel - Citrawati, F.; Quadir, Md Zakaria; Munroe, P. (Nippon Tekko Kyokai, 2017)
© 2017 ISIJ. In this investigation, a grain oriented silicon steel was annealed from a starting state of its primary recrystallized condition by varying time, temperature and heating rate to elucidate the phenomena that occur during the secondary recrystallization growth of Goss grains. Goss secondary recrystallization occurs in a temperature range from 900 to 1 000°C. Using a slow rate of heating (5°C/minute) to the annealing temperature yields more scattering in the Goss orientation during the early stages of secondary growth, compared with rapid heating to the annealing temperature in a preheated furnace. Irrespective of the early stage annealing events, after extended annealing to 300 minutes, Goss texture dominates through both rapid and slow heating annealing. Goss growth starts from the sub-surface regions of the sheet, where the concentration of ?-fibre grains is high. At a higher annealing temperature (1 000°C) faster Goss growth occurs at more frequent sites and, as a result, when the process is completed the average size of Goss grains are smaller than that observed through annealing at 900°C. These investigations were conducted by annealing in an air-circulating furnace followed by extensive orientation measurements through electron backscattered diffraction (EBSD) in a field emission gun scanning electron microscope (FEG SEM) and analysis using a transmission electron microscope (TEM).